Unified two-way shear model for steel and FRP-RC slabs: Evaluation and reliability calibration - Ahmad Tarawneh; Roaa J. Alawadi; Hanady Almahmood; Eman Saleh; Aya Al-Asi; Abdullah Alghossoon (Results in Engineering, 2024)
This study introduces a unified two-way (punching) shear design model for concrete reinforced with slabs steel- and FRP bars. The unified model modifies the ACI 318-19 punching shear model to account for the axial stiffness of the tension reinforcement by providing a new modification term (ρ Ereft./Ec)0.26, representing the reinforcing ratio multiplied by the elastic modular ratio of longitudinal bars to concrete. The unified punching shear model has been evaluated over two experimental datasets: FRP-RC slabs (145 specimens) and steel-RC slabs (390 specimens). A comparative assessment between the ACI 440.11-22, CSA S806, JSCE, and the proposed models to test their generalization abilities for slabs reinforced with both types of reinforcement. The assessment indicated a similar performance of the proposed model to the CSA S806 and the JSCE models in terms of statistical measures. The ACI 440.11–22 showed a high average strength ratio (Vexp./Vpred.) of 1.83. However, the ACI and the CSA models showed reduction in the conservatism at high reinforcement axial stiffness. In addition, reliability analysis using Monte Carlo simulation indicated that the unified punching shear model provides a satisfactory safety level with a reliability index between 3.5 and 4.0 for both steel and FRP-RC slabs.